ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KERUSAKAN BAN PADA UNIT DUMP TRUCK DI PT X - Muhammad Ramadhan Anshori; Aqli Mursadin; Rudi Siswanto (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2018)
Tire is important component of a Dump Truck. For transporting material from the loading point and fleet to disposal Dump Truck performance is required. Trouble On the tire will interfere the unit performance. Month period data from January to March show the amount of failure to the unit HD785-7 dump truck tire which can indirectly interfere the performance of the unit. Therefore, analysis of two key performance indicator (KPI) that tread utility ratio (TUR) and lifetime must be done to find the factors that cause failure, as well as find out whether there is a relationship between lifetime and TUR against different types of failure that occurred by using logistic regression. From the analysis, it is known that the tire KPI has yet to reach a given target, the main factor of tire performance has yet to reach the target is human error, operator Dump Truck and Excavator by 44%, from the results of logistic regression analysis of the data for 3 months it is known that the relationship LifeTime and TUR against various types of failure is not significant because Chisq value is greater than the value of 0.05 pr. (5%).